Algoritma Genetika untuk Meningkatkan Keakuratan Segmentasi Pelanggan listrik - Hadi, Sasongko Pramono (2011)
Customer segmentation, In a context of marketing, is a tool to support a company to provide unique needs of specific customer groups. In the power market, one of significant customer requirements appears i.e. power reliability. Considering the and responding to attitudes and behavioral factors of different groups of costumers can help the supplier to make marketing decissions. In this study a clustering technique with Genetic Algorithm (GA) is used to segment the electrical power market in Jakarta, Indonesia, from the customers' point of view. The research in this paper applied K-means clustering whose initial seeds are optimized by GA. The process of segmentation is also compare with other clustering algorithms k-means. The results revealed that GA based clustering technique may improve segmentation performance i.e. acuracy in comparison to other typical clustering algorithms.